Nutrition Counseling among Patients with Gout - Susyani Susyani; Desvianti Desvianti (International Journal of Public Health Science (IJPHS), 2017)
Hyperuricemia (high levels of uric acid in the blood) can cause a buildup of monosodium urate crystals. Sudden increase may lead to gout attacks. Consumption of an unbalanced diet, intake of proteins containing high purine is one of the factors that affect gout arthritis. Based on data from medical records at the hospital Mohamad Palembang Hoesin and increase in the number of visits patients with gout, the cumulative incidence of gout reached 22 % after 5 years, the uric acid levels > 9 mg / dL. One of the efforts to help clients change behavior and accelerate the healing process that nutritional counseling is conducted face to face using leaflets media. The purpose of this study was to determine the effectiveness of low-purine diet counseling against uric acid levels in gout patients who were treated at the Hospital dr. AK Gani Palembang. Is a quasi-experimental study design, this study indicated that nutrition counseling with low-purine diet will help to change the behavior of people with gout in the diet to accelerate the reduction in uric acid levels. The average reduction in uric acid levels after being given a lowpurine diet counseling that is equal to 1.6 mg/dL and concluded that giving low-purine diet counseling are effective in lowering uric acid levels in patients with gout. Based on these results, low-purine diet counseling should be offered to patients with gout in an effort to motivate behavior change and reduction in uric acid levels. Nutrition counseling with Low-purine diet in patients with gout can change the eating habits of patients who eventually decreased the levels of uric acid.